PERKEMBANGAN PSIKOLOGI ANAK KARENA DAMPAK BULLYING - Fadillah, Ahmad Arif; Meidanty, Cindy Arlinda; Haniifah, Fiilzah; Utami, Nabela Kanti; Amalia, Novia; Endjid, Prissis; Hasanah, Rihlah; Rahman, Rif’an Maulana; Kausar, Rizky Ahmad; Setiawan, Thoni Putra (Transpublika Publisher, 2022)
This research is motivated by the large number of mass media reporting on acts of bullying committed by children and adolescents today. This research was conducted by the education management course. The bullying experienced by the victim is in the form of verbal and physical bullying. The purpose of this study is to find out how the psychosocial impact of bullying victims in everyday life, as well as to provide education to parents of victims to be more sensitive to the developments and problems faced by children, especially to continue to monitor children's interactions. The results of this study can be concluded, namely that bullying cases have a negative impact on victims of bullying, namely first, children who are victims of bullying are anti-social towards the playing environment, victims withdraw from the social environment and to interact socially. Being indifferent to what is happening in the surrounding environment. Second, the impact on the victim's psychology is that there is a deep depression that begins with a sense of trauma experienced and then turns into depression.